EVALUATION OF HEMATOLOGICAL MARKERS FOR DIAGNOSTIC SIGNIFICANCE IN HELICOBACTER PYLORI INFECTION - SHAHID, S; ABBASI, S; ZULFIQAR, S; ABRAR, Z; AHMAD, W; USMAN, M (Biological and Clinical Sciences Research Journal, 2024)
Hematological parameters provide valuable insights into various health conditions. This study aimed to evaluate and compare haematological parameters between patients and healthy controls, assessing conditions related to specific haematological markers. Objective: To identify significant differences in haematological parameters, including haemoglobin (HGB), red blood cell count (RBC), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), and red cell distribution width (RDW), between patients and controls. Methods: A comparative cross-sectional study was conducted, including 60 patients and 60 healthy controls. Key haematological parameters were measured and statistically analyzed to evaluate differences between the groups. Additionally, the distribution of conditions such as anaemia, low MCV, and other haematological abnormalities was assessed. Results: Significant differences were observed in several parameters. Patients exhibited lower mean HGB (12.2 ± 1.3 g/dL vs. 14.32 ± 1.46 g/dL, p=0.01), MCV (84.1 ± 2.11 fl vs. 89.16 ± 3.53 fl, p=0.04), MCH (24.6 ± 4.16 pg vs. 28.13 ± 0.87 pg, p=0.001), and MCHC (30.2 ± 2.10 g/dL vs. 31.58 ± 0.24 g/dL, p=0.01) compared to controls. RBC counts were higher in patients (4.42 ± 0.32 × 10^6/µL vs. 3.87 ± 1.53 × 10^6/µL, p=0.02), while RDW showed no significant difference (13.7 ± 1.032% vs. 12.4 ± 1.22%). Regarding conditions among patients: 13% exhibited low HGB, while 9% had normal HGB levels. RBC levels were normal in 92% of patients, with 5% showing low values. HCT levels were predominantly normal (94%), with 12% showing low values. MCV was normal in 87%, with 13% showing low levels. MCH was normal in 85%, with 2% showing low levels. MCHC was normal in 96%, with 1% showing high levels. RDW was normal in 98%, with only 1% showing low levels. Conclusion: The study highlights significant haematological alterations in patients, including lower HGB, MCV, MCH, and MCHC, with normal RBC and HCT levels in most cases. These findings suggest a trend toward anaemia and related conditions in the patient population. Further research is necessary to explore the clinical implications of these alterations.